Dividends and management promotion—Evidence from internal labor market in an emerging economy. (22nd May 2020) - Yang, Dan; Cheng, Linyin; Wang, Guojun; Wang, Yuetang
Abstract: Top management in state‐owned enterprises (SOEs) works in a typical internal labor market and seeks political promotion after the tenure. By using a sample of Chinese listed SOEs for 2003–2013, this paper documents that top management in SOEs has motivations to trade‐off its own promotion through increasing dividend payout, and the evidence becomes more significant when SOEs report better financial performance than their industry averages.